Fauna de microartropodos asociada a los cultivos de olivar y girasol en la provincia de Codoba - Cardenas, A.M.=700 1 Bach, C.
(Es, En)
ilus., 11 ref.
Keywords: FAUNA; ARTROPODOS; MUESTREO; GIRASOL; OLIVO; ESPAÑA